The age of randomized clinical trials: three important aspects of randomized clinical trials in cardiovascular pharmacotherapy with examples from lipid, diabetes, and antithrombotic trials. Issue 5 (2nd November 2020) - Drexel, Heinz; Lewis, Basil S; Rosano, Giuseppe M C; Saely, Christoph H; Tautermann, Gerda; Huber, Kurt; Dopheide, Joern F; Kaski, Juan Carlos; Mader, Arthur; Niessner, Alexander; Savarese, Gianluigi; Schmidt, Thomas A; et al.
Abstract: This review article aims to explain the important issues that data safety monitoring boards (DSMB) face when considering early termination of a trial and is specifically addressed to the needs of clinical and research cardiologists. We give an insight into the overall background and then focus on the three principal reasons for stopping trials, i.e. efficacy, futility, and harm. The statistical essentials are also addressed to familiarize clinicians with the key principles. The topic is further highlighted by numerous examples from lipid trials and antithrombotic trials. This is followed by an overview of regulatory aspects, including an insight into industry–investigator interactions. To conclude, we summarize the key elements that are the basis for a decision to stop a randomized clinical trial (RCT).